2018
DOI: 10.1029/2018jb015866
|View full text |Cite
|
Sign up to set email alerts
|

Source Properties and Triggering Processes of Long‐Period Events Beneath Volcanoes Inferred From an Analytical Formula for Crack Resonance Frequencies

Abstract: Long‐period (LP) seismic events are thought to arise from the oscillations of a fluid‐filled resonator. The fluid properties and resonator geometry of LP sources have been estimated by comparing observed frequencies to those calculated from a crack model. However, simultaneous determinations of crack geometry and fluid properties have been based on time‐consuming crack model simulations. We developed an alternative method to estimate these crack model parameters using a recently proposed analytical formula. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…This particle size broadly matches that of the Húsafell tuffisite, as well as other documented tuffisite veins for which more detailed particle size analysis has been conducted (e.g., Saubin et al, 2016;Heap et al, 2019). A similar model has been proposed at Galeras volcano, with LP events suggested to represent the propagation and increase in volume of a vertical crack injected by a gas-ash mixture (Taguchi et al, 2018). Both the crack volume and mass fraction of gas within the crack were inferred to have decreased as ash was deposited and welded before the next LP event (Taguchi et al, 2021).…”
Section: Tuffisites As a Seismic Sourcesupporting
confidence: 73%
“…This particle size broadly matches that of the Húsafell tuffisite, as well as other documented tuffisite veins for which more detailed particle size analysis has been conducted (e.g., Saubin et al, 2016;Heap et al, 2019). A similar model has been proposed at Galeras volcano, with LP events suggested to represent the propagation and increase in volume of a vertical crack injected by a gas-ash mixture (Taguchi et al, 2018). Both the crack volume and mass fraction of gas within the crack were inferred to have decreased as ash was deposited and welded before the next LP event (Taguchi et al, 2021).…”
Section: Tuffisites As a Seismic Sourcesupporting
confidence: 73%
“…However, it is possible that the first two spectral peaks in the seismic data do not correspond to the fundamental mode and first higher mode if any of them are not properly excited. For instance, previous studies of VLP and LP events (Kumagai, 2006;Taguchi et al, 2018Taguchi et al, , 2021 indicated that the observed lowest frequencies were not the fundamental mode. To examine this hypothesis, we compute the frequency ratios between the first 5 resonant modes and the ratios between the first 4 longitudinal modes of a rectangular crack with varying C L and aspect ratios α (see Tables S7-S10 in the Supporting Information S1).…”
Section: Application To Vlp Seismic Signals During the Mayotte Volcan...mentioning
confidence: 95%